PERTUMBUHAN JAMUR KUPING (AURICULARIA POLYTRICA) PADA DELAPAN JENIS KAYU - Sihati Suprapti; Ginuk Sumarni (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
Ear mushroom (Auricularia polytrica) was cultivated on logs of eight wood species i.e. hamerang (Ficus grossularoides Burn. f.), jeungjing (Albizia falcataria (L.) Fosb.), kihuut (Vernonia arborea Ham.), kipiit (Maesa ramentacea Wall.), manii (Maesopsis eminii Engl.), sehang (Ficus padana Burn. f.), seuseureuhan (Piper aduncum L.) and teureup (Artocarpus elastica Reinw. ). The logs were kept slanted on an angle of ± 60° with bamboo supports in shady site under trees at Gunung Bunder, Bogor.The mature mushroom was harvested every day after the growth of the fruiting body. The logs start producing fungus two months after inoculation. The highest harvested was obtained at fourth month of observation. The higher total yield of ear mushroom during the six months observation was obtained from seuseureuhan log (59.537 kg), sehang (28.08 kg), manii (16.056 kg) and hamerang log (14.838 kg) per m3 of log. The lower total yield was obtained from kipiit log (11.2 kg), kihuut (9.813 kg), jeungjing (4.526 kg) and teureup (2.441 kg) per m3 of log.